Nanomaterials in Cosmetics: An Outlook for European Regulatory Requirements and a Step Forward in Sustainability - Ferreira, Laura (2023)
The use of materials and products that improve appearance and provide comfort and well-being goes back to the beginning of civilization. Cosmetics is an evolving market that has increasingly focused on innovative technological approaches. Nanotechnology is one of the most revolutionary and promising fields for the development of novel and enhanced cosmetic products, owing to the remarkable multifunctional characteristics and effects of nanomaterials (NMs). Their application, however, also raises potential safety concerns. Some of these concerns can be addressed by determining the type of NMs used, as well as their stability, potential for skin absorption, route of exposure, and how they are formulated into cosmetic products. To guarantee such safety, cosmetic products containing NMs, must comply with European regulatory provisions, particularly the European Regulation (EC) n. 1223/2009 of the European Parliament and of the Council. Hence, this review comprises all the particularities of NMs, their influence on human health, challenges towards environmental sustainability, and strategies to harmonize policies with the aim to normalize their application in cosmetics.